Evaluación de biofertilizantes de micorrizas nativas y comerciales en el cultivo de fréjol (Phaseolus vulgaris L.), en la quinta experimental la Argelia. Loja, Ecuador. - Aguilar Asanza, Julio César (2023)
This research was proposed in order to increase the low yields of the bean crop (Phaseolus vulgaris L.) in Ecuador, employing biofertilizers of arbuscular mycorrhizal fungi (AMF) in the Blanco Belén bean variety, four treatments were evaluated [T1: control (SM), T2: commercial liquid mycorrhiza (MLC), T3: native mycorrhiza (MN) and T4: solid commercial mycorrhiza (MSC)] in a completely randomized block design with five replicates, each with 25 plants and with one planting density of 0.30 x 0.50 m. The main objectives of the research were to define the efficiency of mycorrhizal biofertilizers in phenological development and crop yield in the La Argelia Experimental Fifth of the National University of Loja. The following variables were measured: days for germination, days to leaves, plant height, stem diameter, number of leaves, days to flowering, number of flowers, days to green harvest, number of pods, length of pod, yield (kg/ha) in green pod and number of nodules, the percentage of AMF colonization was also evaluated. The results show that the application of mycorrhizal biofertilizers increased crop yield by 29 % compared to the control. The MLC, MN and MSC treatments exceeded 50 % colonization in the roots and arbuscules, vesicles, spores and hyphae were observed in the roots of the culture. The investigation demonstrates that the symbiosis between fungus and root is possible in the bean plant through the use of native and commercial mycorrhizal products, which favours phenological development and crop yield. Keywords: mycorrhizal biofertilizers, mycorrhizal spores, native inoculum, beans.